Development of ion sensitive field effect transistor device for real time growth detection of mycobacterium tuberculosis - Pawasuth Saengdee (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The development of rapid and highly reliable sensor is essential for preventing the transmission of M. tuberculosis which is a major health issue in developing countries. In this study, the ion sensitive field effect transistor (ISFET) was developed for the detection of Ag85B protein. This protein is highly secreted during M. tuberculosis growth in liquid media. As the efficiency of ISFET depends on the type of sensing membrane and immobilization method, both of these factors were studied to achieve the optimal condition for ISFET fabrication. Ag85B ImmunoFET was developed by immobilizing monoclonal antibody against Ag85B protein (anti-Ag85 mAb clone AM85B-5 and AM85B-8) onto sensing membrane. The linearity of AM85B-5 modified ImmunoFET is 0.12 -1 ?g/ml and 0.18-1 ?g/ml for AM85B-8 modified ImmunoFET. Then, AM85B-5 modified Ag85B ImmunoFET was employed for the detection of native Ag85B protein in culture filtrate. The result showed AM85B-5 modified Ag85B ImmunoFET was highly specific to native Ag85B protein of M. tuberculosis than other mycobacteria species. Therefore, AM85B-5 modified Ag85B ImmunoFET could be embedded into culture system for real-time growth monitoring M. tuberculosis, however, its performance should be improved before applying into the culture system to obtain a more effective M. tuberculosis sensor.